2008
DOI: 10.1007/s00540-008-0656-9
|View full text |Cite
|
Sign up to set email alerts
|

An adult patient with Kabuki syndrome presenting with Henoch-Schönlein purpura complicated with pulmonary hemorrhage

Abstract: We present a case of a 33-year-old woman with Kabuki syndrome (KS) presenting with Henoch-Schönlein purpura (HSP). She was admitted to our hospital with a brain abscess in the lateral ventricle and meningitis. She had been diagnosed with KS. Skin eruptions had appeared on her lower extremities, with arthralgia, cough, and hemoptysis. She suddenly developed pulmonary hemorrhage and respiratory failure. We intubated her trachea and started mechanical ventilation in the intensive care unit (ICU). Skin biopsy reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Weir et al () highlighted an association between Kabuki syndrome and premature atherosclerosis, suggesting that the syndrome itself may contribute to the predisposition also in absence of classical different risk factors. A case report of Henoch‐Schonlein purpura causing thrombosis has also been reported (Oto et al, ). In addition, the growth hormone deficiency described in patients with Kabuki syndrome (Devriendt, Lemli, Craen, & de Zegher, ) should be mentioned as an additional risk factor, since it known to be associated with endothelial dysfunction, increased intima medial thickness and reduced aortic distensibility.…”
Section: Discussionmentioning
confidence: 91%
“…Weir et al () highlighted an association between Kabuki syndrome and premature atherosclerosis, suggesting that the syndrome itself may contribute to the predisposition also in absence of classical different risk factors. A case report of Henoch‐Schonlein purpura causing thrombosis has also been reported (Oto et al, ). In addition, the growth hormone deficiency described in patients with Kabuki syndrome (Devriendt, Lemli, Craen, & de Zegher, ) should be mentioned as an additional risk factor, since it known to be associated with endothelial dysfunction, increased intima medial thickness and reduced aortic distensibility.…”
Section: Discussionmentioning
confidence: 91%
“…Totally 76 cases of KS were reported to be associated with congenital heart defects by 19 reports [6,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Of them, the gender was expressed in 37 patients including 17 males and 20 females with a male-to-female ratio of 0.85:1.…”
Section: Resultsmentioning
confidence: 99%
“…Vera et al [Teixeira et al, ] described recurrent latex allergy after small surgery in an 11‐year‐old girl with KS. Jun et al [Oto et al, ] reported a 33‐year‐old female with KS and accompanying Henoch–Schönlein purpura. More recently, Lindgren et al [] described a female with disrupted KDM6A function caused by a translocation at intron 2 who presented with an eczematoid rash on her cheeks and thighs and allergy to sulfa drugs, vancomycin, and ibuprofen.…”
Section: Discussionmentioning
confidence: 99%